Nutritional composition of germinated brown rice porridge - Abdul Kadir, Khairul Kamilah; Azlan, Azrina; Amom, Zulkhairi; Mohd Esa, Norhaizan; Ismail, Maznah (Global Science Books, 2008)
In industrialized and developed countries more people are seeking preventive medicine rather than a curative approach. Considering germinated brown rice (GBR) is dense in dietary fibers, nutrients and antioxidants, the development of instant nutritious GBR porridge (GBRP) was proposed. The nutrient composition and fatty acid profile of GBRP were investigated. A comparison between GBRP, white rice porridge (WRP) and commercial porridge (CP) was carried out. GBRP contained significantly higher (P<0.05) ash (0.86 g/100 g sample) and dietary fiber (8.03 g/100 g sample) contents compared to WRP (0.81 g/100 g and 4.84 g/100 g sample) and CP (0.74 g/100 g sample and 6.46 g/100 g sample). Higher ash content was correlated with a higher level of sodium, calcium, potassium and magnesium. Protein content of GBRP was also significantly higher (P<0.05; 1.74 g/100 g sample) than CP (1.17 g/100 g sample). Interestingly, GBRP had 0.17 g/100 g sample of fat, which is four-fold higher than in WRP (0.04 g/100 g sample) and CP (0.03 g/100 g sample). The higher percentage of fat was correlated to a higher level of unsaturated fatty acids (USFA) than saturated fatty acids (SFA). The results from the present study revealed a higher potential of GBRP as a healthier option that is abundant in health-promoting compounds.